Mewujudkan Kelas Inklusif dan Adaptif Melalui Perencanaan Pembelajaran Berdiferensiasi di SMP - Junaidin Junaidin; Mirna Mirna (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2025)
This article takes a deep dive into the concept of differentiated instruction as a key strategy for creating inclusive and adaptive classrooms in junior high schools. Using a literature review method, the discussion focuses on how teachers can develop learning plans that respond to students' diverse readiness levels, interests, and learning styles through modifications to content, processes, and learning outcomes. This study demonstrates that differentiation is not merely a technical approach but a pedagogical approach that places students' needs at the center of learning. Within the context of the Merdeka Curriculum, differentiated learning serves as a crucial foundation for delivering fair and meaningful education, supported by diagnostic assessments and flexible planning. This article recommends strengthening teachers' capacities, fostering professional collaboration, and ensuring systemic support from educational institutions as essential prerequisites for the optimal and sustainable implementation of differentiated learning.